Influence of arbuscular mycorrhizal fungi on biological control of coffee leaf rust (Hemileia vastatrix Berk. & Broome) - Solís Leyva, Reynaldo (2023)
Inoculating plants with arbuscular mycorrhizal fungi (AMF) protects host plants against biotic stressors such as diseases. Therefore, the objective of this study was to evaluate the influence of arbuscular mycorrhizal fungi in the biological control of coffee leaf rust (CLR) infections. The research involved two varieties of coffee (Caturra and Pache) and three inocula of AMF: Moyobamba (Acaulospora mellea, Acaulospora sp.1, Glomus geosporum, Glomus sp.1, andGlomus sp.2), El Dorado (Acaulospora rugosa, Acaulospora spinosissima, Acaulospora lacunosa, Glomus sinuosum andAmbispora appendicula) and Huallaga (Acaulospora mellea, Acaulospora sp.1, Acaulospora sp.2, Glomus macrocarpum and Glomus sp.2), in addition to a control treatment without application of AMF (non-AMF). Inoculation of vegetatively propagated coffee plants with AMF was observed to induce tolerance to CLR. The incidence of CLR in non-AMF coffee plants was 43.7 %, while in the coffee plants subjected to the inocula Moyobamba, El Dorado and Huallaga, the incidences were 22.1, 22.7 and 13.2 %, respectively. Likewise, the severity in non-AMF coffee plants was 34.8 %, while in the coffee plants subjected to the three kinds of inocula, the severities were 21.1, 20.4 and 12.0 %, respectively. Thus, mycorrhizal inoculation of coffee plants at the nursery stage reduces the negative effect of CLR infection after the plants are taken to field conditions, representing a sustainable option for their biological control.